Polyphase Magmatism During the Formation of the Northern East Greenland Continental Margin. Issue 8 (14th August 2019) - Franke, D.; Klitzke, P.; Barckhausen, U.; Berglar, K.; Berndt, C.; Damm, V.; Dannowski, A.; Ehrhardt, A.; Engels, M.; Funck, T.; Geissler, W.; Schnabel, M.; et al.
Abstract: New marine geophysical data acquired across the partly ice‐covered northern East Greenland continental margin highlight a complex interaction between tectonic and magmatic events. Breakup‐related lava flows are imaged in reflection seismic data as seaward dipping reflectors, which are found to decrease in size both northward and southward from a central point at 75°N. We provide evidence that the magnetic anomaly pattern in the shelf area is related to volcanic phases and not to the presence of oceanic crust. The remnant magnetization of the individual lava flows is used to deduce a relative timing of the emplacement of the volcanic wedges. We find that the seaward dipping reflectors have been emplaced over a period of 2–4 Ma progressively from north to south and from landward to seaward. The new data indicate a major post‐middle Eocene magmatic phase around the landward termination of the West Jan Mayen Fracture Zone. This post‐40‐Ma volcanism likely was associated with the progressive separation of the Jan Mayen microcontinent from East Greenland. The breakup of the Greenland Sea started at several isolated seafloor spreading cells whose location was controlled by rift structures and led to the present‐day segmentation of the margin. The original rift basins were subsequently connected by steady‐state seafloor spreading that propagated southward, from the Greenland Fracture Zone to the Jan Mayen Fracture Zone. Key Points: Polyphase Cenozoic volcanic rifting and consecutive emplacement of breakup‐related lava flows along the northern East Greenland margin Breakup along restricted margin segments is followed by north to south directed progressive opening of the Greenland Sea Widespread post‐middle Eocene (<40 Ma) offshore magmatism, associated with the breakup of the Jan Mayen microcontinent from East Greenland